The Reluctant Feminist: Angela Merkel and the Modernization of Gender Politics in Germany - Mushaben, Joyce Marie (My University, 2018)
Academic studies regarding the impact of various forms of gender representation focus largely on quantitative evidence that women in power can make a difference, downplaying qualitative case studies that can establish causal links between women's participation in government and better policies for women. Analyzing policy changes initiated by Germany’s first female Chancellor since 2005, the paper argues that despite her CDU-affiliation, Angela Merkel has contributed more to gender equality in Germany than all previous chancellors, even though she refuses to label herself a feminist. The author explores three factors shaping Merkel's reluctance to embrace the (western dominated) feminist label, e.g., her socialization under a diametrically opposed GDR gender regime, her preference for data-driven policy learning, her aversion towards “ideological” framing, coupled with a tendency to pursue mixed motives, respectively. The paper concludes with recent examples geared towards leveling the global gender playing-field, attesting to her willingness to embrace transformational representation.
Keywords: Angela Merkel; Politik; Repräsentation; ddc:320 Politikwissenschaft; ddc:320